2019
DOI: 10.1016/j.thromres.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic and non-genetic risk factors for venous thromboembolism in glioblastoma – The predictive significance of B blood group

Abstract: Introduction: Venous thromboembolism (VTE) is a common problem among patients with glioblastoma multiforme (GBM) and with some other cancers. Here, we evaluated genetic and non-genetic potential risk factors for VTE among GBM patients. Materials and methods:A cohort of 139 patients treated with concomitant radiotherapy and temozolomide were included in the study. Next generation sequencing and genotyping approaches were applied to assess genetic risk factors in the haemostatic system. Clinical data including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…From these, we removed 40 duplicates and excluded non-relevant studies, review articles, meeting abstracts, case reports, replies, editorials or commentaries, and studies in languages other than English. This left 40 studies for review, from which we identified nine studies for systematic review [13][14][15][16][17][18][19][20][21] and five studies [14,15,[17][18][19] for qualitative meta-analysis (Figure 1). cluded in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these, we removed 40 duplicates and excluded non-relevant studies, review articles, meeting abstracts, case reports, replies, editorials or commentaries, and studies in languages other than English. This left 40 studies for review, from which we identified nine studies for systematic review [13][14][15][16][17][18][19][20][21] and five studies [14,15,[17][18][19] for qualitative meta-analysis (Figure 1). cluded in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…In addition, the timing of diagnostic evaluation of patients for venous thromboembolism was based on symptom presentation and/or clinical evaluation, and most of the studies did not follow a precise protocol. Multivariate logistic regression analyses were not performed in three studies [13,16,20], and although Wang et al evaluated the association of venous thromboembolism with ABO blood type, they reported a higher risk of each non-O blood type (A/B/AB) compared to O blood type (OR (95% CI); A: 2.072 (1.204-3.566), B: 1.944 (1.020-3.873), AB: 2.706 (1.432-5.114)). These four studies were excluded from our meta-analysis.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“… 97 Similarly, the odds of VTE in those with glioblastoma, pancreatic cancer, and prostate cancer were increased in those with a non-O vs O blood type, similar to the ABO effect in the cancer-free population. 98 , 99 , 100 …”
Section: Vwf In Special Cases Of Vte Diseasementioning
confidence: 99%
“…The association of blood group with VTEs in glioma patients has been discussed controversially. Whereas B blood group was found to be predictive for VTEs in a cohort of 139 glioblastoma patients [13], this was not confirmed in a prospective study of patients diagnosed with glioma, including glioblastoma [7]. Elevated factor VIII levels [7] and low platelets or high leukocytes [14] have been reported to increase the risk of VTEs in glioblastoma patients.…”
Section: Introductionmentioning
confidence: 99%